Pemulihan Penyangatan Gadolinium Akhir dan Pemetaan Jantung T1-T2 dengan Kriteria Lake Louise pada Pasien Miokarditis Akut: Serial Kasus - Andriono, Prasetyo (PT Kalbe Farma Tbk., 2024)
Myocarditis is a condition characterized by inflammation in the myocardium. Myocarditis is difficult to diagnose, due to its multiple, heterogeneous manifestations with many differential diagnoses. T1 and T2 cardiac mapping were added as a criterion in the revised Lake Louise Criteria (LLC). The revised criteria have been reported to have higher sensitivity. We included two patients diagnosed with myocarditis based on the revised LLC. All patients were diagnosed using cardiac magnetic resonance (CMR), which includes late gadolinium enhancement (LGE) and T1-T2 mapping. LGE is a technique frequently used in CMR to visualize cardiac tissue, whichis most sensitive to fibrosis. Revised LLC includes quantitative measures of T1 and T2 value, and T1-T2 mapping is advantageously related to its ability to quantitatively assess myocardial abnormalities. CMR using LGE combined with T1-T2 mapping allows the diagnosis of myocarditis. Recovery of T1 and T2 values during follow-up allows quantitative measurement of patients’ condition and treatment success.